Pengaruh Kepemimpinan Etis dan Keadilan Organisasional terhadap Perilaku Etis Karyawan pada PT X - Ratu Bilqis Arifiani; Suryanto Sosrowidigdo; Siti Nurjanah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Employee ethical behavior plays an essential role in preserving organizational integrity, promoting professional conduct among employees, and improving sustainable organizational performance, especially within operational divisions where work demands and ethical dilemmas are relatively high. This research was conducted to examine both the individual and joint influences of ethical leadership (X1) and organizational justice (X2) on employee ethical behavior (Y) among operational employees at PT X. A quantitative study involving 42 respondents was analyzed using multiple linear regression in IBM SPSS Statistics 25 based on data collected through observations, interviews, and questionnaires. The analysis revealed that ethical leadership positively and significantly affects employee ethical behavior (t = 5.612; sig. = 0.000). Employee ethical behavior was found to be positively and significantly influenced by organizational justice (t = 6.723; sig. = 0.000). The simultaneous testing further demonstrated that ethical leadership and organizational justice collectively exert a significant effect on employee ethical behavior (F = 16.911; sig. = 0.000). The regression model produced an Adjusted R² value of 0.436, suggesting that 43.6% of the variation in employee ethical behavior can be explained by the two independent variables, whereas the remaining 56.4% is attributable to factors beyond the scope of this research.